Formation Process and Mechanical Deformation Behavior of a Novel Laser-Printed Compression-Induced Twisting-Compliant Mechanism. (August 2022) - Gao, Jie; Gu, Dongdong; Ma, Chenglong; Dai, Donghua; Xi, Lixia; Lin, Kaijie; Gao, Tong; Zhu, Jihong; Du, Yuexin
Abstract: A novel compression-induced twisting (CIT)-compliant mechanism was designed based on the freedom and constraint topology (FACT) method and manufactured by means of laser powder bed fusion (LPBF). The effects of LPBF printing parameters on the formability and compressive properties of the laser-printed CIT-compliant mechanism were studied. Within the range of optimized laser powers from 375 to 450 W and with the densification level of the samples maintained at above 98%, changes in the obtained relative densities of the LPBF-fabricated CIT-compliant mechanism with the applied laser powers were not apparent. Increased laser power led to the elimination of residual metallurgical pores within the inclined struts of the CIT mechanism. The highest dimensional accuracy of 0.2% and the lowest surface roughness of 20 μm were achieved at a laser power of 450 W. The deformation behavior of the CIT-compliant mechanism fabricated by means of LPBF exhibited four typical stages: an elastic stage, a heterogeneous plastic deformation stage, a strength-destroying stage, and a deformation-destroying stage (or instable deformation stage). The accumulated compressive strain of the optimally printed CIT mechanism using a laser power of 450 W went up to 20% before fracturing, demonstrating a large deformation capacity. The twisting behavior and mechanical properties were investigated via a combination of finite-element simulation and experimental verification. An approximately linear relationship between the axial compressive strain and rotation angle was achieved before the strain reached 15% for the LPBF-processed CIT-compliant mechanism.